Effect of physical factors on activity amillolitical enzymes of salads of grain culture - Косоголова, Л. О.; Лошицький, П. П.; Турбовська, С. В.; Самчук, Н. В. (Problems of Environmental Biotechnology, 2019)
The article defines the influence of temperature and active acidity at a temperature of 74 °C on the amylolytic activity of wheat malt enzymes. The optimal saccharification temperature is 76 °C, and the pH is 6,8. The influence of electromagnetic radiation of the radio frequency range: kilometers (low frequency (LF)) and millimeter (extreme high-frequency (EHF)) waves on the activity of amylolytic enzymes of barley malt has been established. It is proposed to use extreme high-frequency irradiation to increase the amylolytic activity of barley malt enzymes, the exposure time is 5 minutes.